2017
DOI: 10.1039/c7ra06712g
|View full text |Cite
|
Sign up to set email alerts
|

Soot oxidation performance with a HZSM-5 supported Ag nanoparticles catalyst and the characterization of Ag species

Abstract: A HZSM-5 supported Ag nanoparticles catalyst, which has a Si/Al ratio of 1500, is synthesized by a simple impregnation method for soot oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Ag in both materials, EXAFS χ­( k ) (Figure S50) and |χ­( R )| (Figure S63), suggests a distribution of supported species formed that could lead to destructive interference in the EXAFS. Similar low-amplitude EXAFS oscillations have been reported by Ruan et al for Ag species supported on H-ZSM5, in which case the authors concluded a combination of Ag + ions in the zeolite framework and Ag nanoparticles . The EXAFS fit for Ag/LMO indicates a mixture of oxidized and metallic Ag (Table S10), although uncertainties preclude direct structure assignment due to low fitting range ( k : 3–8 Å –1 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Ag in both materials, EXAFS χ­( k ) (Figure S50) and |χ­( R )| (Figure S63), suggests a distribution of supported species formed that could lead to destructive interference in the EXAFS. Similar low-amplitude EXAFS oscillations have been reported by Ruan et al for Ag species supported on H-ZSM5, in which case the authors concluded a combination of Ag + ions in the zeolite framework and Ag nanoparticles . The EXAFS fit for Ag/LMO indicates a mixture of oxidized and metallic Ag (Table S10), although uncertainties preclude direct structure assignment due to low fitting range ( k : 3–8 Å –1 ).…”
Section: Resultssupporting
confidence: 81%
“…Ag/MnO 2 could be fit with oxygen in the first shell, but with manganese in the second shell (Table S10), suggesting that species on the support may be more isolated than on LMO. Despite fit uncertainties, Ag–O bond lengths in Ag/MnO 2 and Ag/LMO (Table S10) are on average longer than estimated lengths for Ag + –O bonds in Ag 2 O (approximately 2.1 Å); however, coordination numbers fit for both materials support a low coordinate structure, more akin to linear Ag + .…”
Section: Resultsmentioning
confidence: 88%
“…The lack of features in the Ag K-edge XANES for AgNO 3 and Ag-MOR beyond the absorption edge has previously been attributed to the significant positional disorder of Ag, which suppresses spectral features . Similar to Ag-MOR, Ag-exchanged levyne and HZSM-5 zeolites show only broad spectral features in Ag K-edge XANES. , …”
Section: Resultsmentioning
confidence: 92%
“…60 Similar to Ag-MOR, Ag-exchanged levyne and HZSM-5 zeolites show only broad spectral features in Ag Kedge XANES. 61,62 The data in Table 2 and Figure 6 show that the sorbents prior to iodine loading contained mostly Ag + with some reduced Ag 0 being present, even though no steps were implemented in the procedure to actively reduce the Ag + to Ag 0 . This has been seen in some of our previous studies using a similar AgNO 3 exchange process to incorporate Ag into porous aluminosilicate scaffolds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Obviously, the Ag K-edge RSF profiles of the Ag-supported catalysts are similar to that of Ag foil with the Ag−Ag coordination peak at 0.270 nm, suggesting the metallic state of the Ag species in Ag/Co-LDO-H and Ag/Co-LDO-C. Moreover, the Ag−Ag coordination peak in Ag/Co-LDO-H is broader and weaker than that in Ag/ Co-LDO-C, indicating that the smaller-sized Ag NPs are highly dispersed on Ag/Co-LDO-H. 38 It is in agreement with the XRD results in Figure 1b. Table 1 provides the EXAFS parameters of the first Ag−Ag coordination shell for the Agsupported catalysts.…”
Section: Kinetic Measurementsmentioning
confidence: 97%